Method of treating or preventing ischemia-reperfusion injury - BAZ MORELLI ADRIANA; VIKSTROM INGELA; PEARSE MARTIN (2020)
The present disclosure relates to a method for preventing or treating ischemia-reperfusion injury in a subject the method comprising administering a compound that inhibits granulocyte colony stimulating factor (G-CSF) signaling. In some examples, the ischemia-reperfusion injury is due to or associated with tissue or organ transplantation. In some examples, the compound is an antibody. 本公开涉及用于防止或治疗受试者的缺血-再灌注损伤的方法，所述方法包括施用抑制粒细胞集落刺激因子(G-CSF)信号传导的化合物。在一些示例中，缺血-再灌注损伤是由于组织或器官移植或与组织或器官移植相关。在一些示例中，所述化合物是抗体。